Casa A.C.H. - Larrazabal-Servente (2006)
La casa podría definirse como la conjunción de dos volúmenes, diefrenciados material y funcionalmente.
Keywords: LARRAZABAL, VICTORIA; SERVENTE, SANTIAGO; ARGENTINA; NEUQUEN; SAN MARTIN DE LOS ANDES; VIVIENDAS UNIFAMILIARES; VIVIENDAS DE MONTAÑA; CONSTRUCCION; PIEDRA; ESTRUCTURAS DE MADERA